Inclusion and holes detection in 3D objects using numerical modeling and neural networks - Havdulskyi, Roman; Zhuravchak, Liubov (Technology audit and production reserves, 2026)
The object of research is a stationary heat-conduction process in three-dimensional heterogeneous media which components are in ideal thermal contact. The addressed problem is the difficulties in detecting, localizing, and classifying inclusions in 3D objects. Most methods rely on employing active thermography which produces data as time-dependent sequences. Both capturing and processing it is quite costly and resource required. The paper proposes a hybrid approach that relies on steady-heat thermograms, which are significantly easier and cheaper to capture. The developed approach uses one of the variants of the indirect near-boundary element method (INBEM), SOTA detectors (YOLO 11n and 12n), and a custom depth head based on ConvNeXt V2. Additionally, the paper showed that attention-centric architecture is promising for processing steady heat images. INBEM with near-boundary elements in the form of families of points achieves an execution time of approximately 50 seconds per sample, with a general maximum error of approximately 0.08. This enabled the creation of a large dataset, comprising approximately 130K samples. Additionally, a testing dataset with a size of 7K and slightly different variance is obtained. Both YOLO 11n and 12n showed mAP50:95 metric results on the testing dataset of 85.2% and 89.4%, respectively. The precision/recall for both models are the following: 92.0/92.8 and 92.3/96.3. The depth head showed a MAPE of about 2%. The proposed method focuses on detecting inclusions and holes using steady heat images, so it is suitable for relatively low-cost analysis, as obtaining such data is easier and quicker than collecting time-dependent data. It may be useful to screen slab-like structures, such as photovoltaic panels. Wall diagnostics is one possible future application area, as the work can be extended to semi-infinite objects. Thus, the results may serve as a basis for a low-cost inspection tool.